Implementasi Pancasila terhadap Kasus Korupsi di Indonesia - Rohma Nurunisa; Raya Kamila CB Winata; Rofiq Ibrahim Natis; Zaenul Slam (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Pancasila as the foundation of the state and the national ideology of Indonesia, has a very important function in shaping the moral values, ethics, as well as the attitudes and behavior of state officials. However, the reality of the persistent prevalence of corruption cases reflects a gap between the values contained in Pancasila and the practices of national and state life. This article aims to examine the implementation of Pancasila values in efforts to prevent and address corruption cases in Indonesia. The research method used is a qualitative approach with a literature review method, conducted through an examination of laws and regulations, scientific journals, and various relevant literary sources. The discussion results show that each principle of Pancasila contains anti-corruption values, such as belief in God that instills honesty, humanitarian values that uphold justice, the value of unity that rejects the interests of certain groups, democratic values that emphasize trustworthiness, and the value of social justice for all Indonesian people. However, the implementation of these values has not been carried out optimally due to weak law enforcement and low moral awareness. Therefore, efforts are needed to strengthen Pancasila education, improve the integrity of state officials, and build a collective commitment to realize clean and just governance.